2022
DOI: 10.47102/annals-acadmedsg.2021306
|View full text |Cite
|
Sign up to set email alerts
|

Academy of Medicine, Singapore clinical guideline on the use of sedation by non-anaesthesiologists during gastrointestinal endoscopy in the hospital setting

Abstract: Introduction: In Singapore, non-anaesthesiologists generally administer sedation during gastrointestinal endoscopy. The drugs used for sedation in hospital endoscopy centres now include propofol in addition to benzodiazepines and opiates. The requirements for peri-procedural monitoring and discharge protocols have also evolved. There is a need to develop an evidence-based clinical guideline on the safe and effective use of sedation by non-anaesthesiologists during gastrointestinal endoscopy in the hospital set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…A workgroup, mainly consisting of gastroenterologists and general surgeons, developed guidelines on the use of sedation during gastrointestinal endoscopy, published in the Annals. 2 A total of 16 statements were promulgated based on assessment of the quality of evidence and strength of recommendation. 2 The Council of the College of Anaesthesiologists, Singapore and key opinion leaders are aware of multiple published professional guidelines and position statements on the issue of non-anaesthesiologistadministered propofol (NAAP).…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…A workgroup, mainly consisting of gastroenterologists and general surgeons, developed guidelines on the use of sedation during gastrointestinal endoscopy, published in the Annals. 2 A total of 16 statements were promulgated based on assessment of the quality of evidence and strength of recommendation. 2 The Council of the College of Anaesthesiologists, Singapore and key opinion leaders are aware of multiple published professional guidelines and position statements on the issue of non-anaesthesiologistadministered propofol (NAAP).…”
Section: Dear Editormentioning
confidence: 99%
“…2 A total of 16 statements were promulgated based on assessment of the quality of evidence and strength of recommendation. 2 The Council of the College of Anaesthesiologists, Singapore and key opinion leaders are aware of multiple published professional guidelines and position statements on the issue of non-anaesthesiologistadministered propofol (NAAP). These vary considerably, garnering diverging opinions, 3 with European anaesthesiologists putting forth their strong opinion on the matter.…”
Section: Dear Editormentioning
confidence: 99%
“…The doctors involved had ignored the explicit warnings on the manufacturer's instruction sheet, which indicated that propofol was not to be administered except by someone trained as an anaesthetist or intensivist. 7 Now, I would like to point out some puzzling points in the original article by Ang et al 2 In the Introduction, the authors wrote that the Singapore Ministry of Health (MOH) guideline on the use of sedation by non-anaesthesiologists 8 "does not address the issues pertinent to the hospital setting". However, the authors did not identify what these issues are and how they are addressed in their own article.…”
Section: Sedation In Gastrointestinal Endoscopy In Singaporementioning
confidence: 99%
“…The Academy of Medicine, Singapore (AMS) guideline on the use of sedation by non-anaesthesiologists during gastrointestinal endoscopy in the hospital setting and an accompanying editorial were published in the January 2022 issue of the Annals. 1,2 An evidence-based approach was used with reference made to relevant published literature. The workgroup members were Fellows of A M S compris ing gas trointes tinal s urgeons , gastroenterologists and anaesthesiologists from the public and private sectors.…”
Section: Dear Editormentioning
confidence: 99%
“…The rationale for giving a weak recommendation for NAAP despite the presence of high-quality evidence has been explained in the guideline. 1 The published recommendations are as balanced as possible, based on objective review of scientific evidence. Not all aspects of the recommendations may be immediately applicable as there could be differences in clinical expertise and practice, and barriers to implementation.…”
Section: Dear Editormentioning
confidence: 99%